Analysis of Algebra Structure Implementation Input-Output Applications in the Economic Field - Kamaruddin, Kamaruddin; Panggabean, Ellis Mardiana; Irvan, Irvan (Journal Of Education And Teaching Learning (JETL), 2023)
Mathematicsi isi ai sciencei thati is usefuli ini iall fields, and is also useful in many other sciences. Mathematical models are useful, for example, in ieconomics. One of them uses matrix theory and Gauss-Jordan ielimination in iinput-output ianalysis ito studyi the inter-sectoral iinterconnectedness iof the economy. This study describes the input-output ianalysis. This isi thei implementationi ofi matrixi materiali wherei each sector usesi as inputi the output produced by the output of other sectors, on the other hand the output produced is also the input of other sectors. This research is a qualitative research (library research) with a literary approach. Data collection techniques were carried out by reviewing various books, journals, articles, information or sources deemed appropriate and relevant to the research. Content analysis is used as a data analysis technique whose purpose is to maintain research accuracy and prevent errors in data sources. This is followed by a literature review and a literature review. The results of this study are the transaction matrix, value added ratio of economic activity, technological input-output coefficient matrix, interdependence coefficient matrix and finali demandi usingi the iGauss-Jordani eliminationi method.